THE EFFECT OF INFLATION, HDI, FDI ON ECONOMIC GROWTH IN 10 ASEAN COUNTRIES IN THE PERSPECTIVE OF ISLAMIC ECONOMICS - Maisya, Irin; Malik, Anas; Rahman, Taufiqur (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The economy is also used as evidence of a country's success in assessing achievements and progress towards the level of economic growth, through the system used by the government to regulate and distribute profits from power, services, and goods through economic growth, which results in sustainable economic growth over time. This study aims to determine the effect of inflation variables, human development index and foreign direct investment on economic growth in 10 ASEAN countries in 2015-2023. The method used in this study is a quantitative method. The data used are secondary data obtained from the World Bank. The results of the study using panel data regression with the Random Effect Model test which states the results of the partial test (t) that the inflation variable (X1) has a negative but insignificant effect on economic growth (Y). While the HDI (X2) and FDI (X3) variables have a positive and significant effect on economic growth (Y). From an Islamic economic perspective, Islam sees economic development as a road to human maturity, where material progress must support spiritual maturity. The dream of Islamic economics is to carry out a mission as caliph on earth with the task of making it prosperous.